2022
DOI: 10.1039/d2cc05532e
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of electric field distribution facilitating the Zn anode reversibility

Abstract: The surface morphology of the zinc-metal electrode was modulated using different levels of physical polishing treatment. Modulating the surface scratches homogenized the deposition electric field and reduced the local current...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To evaluate the electrochemical performance of the synthesized CNT@Cu, a half-cell test was conducted using physically etched Zn metal as the counter electrode. 36 Figure 2A illustrates the timevoltage profiles of Zn plating/stripping behavior occurring in the half-cell applying CNT@Cu/bare Cu as a working electrode. Zn was deposited on the working electrode at a current density of 1 mA cm -2 for 1 h, followed by stripping at a cut-off voltage of 0.5 V in the half-cell experiment.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the electrochemical performance of the synthesized CNT@Cu, a half-cell test was conducted using physically etched Zn metal as the counter electrode. 36 Figure 2A illustrates the timevoltage profiles of Zn plating/stripping behavior occurring in the half-cell applying CNT@Cu/bare Cu as a working electrode. Zn was deposited on the working electrode at a current density of 1 mA cm -2 for 1 h, followed by stripping at a cut-off voltage of 0.5 V in the half-cell experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Tang, Liang, Yang, and coauthors reported a light‐fueled DSA system with periodic and dynamic fluorescence fluctuations based on protonated sulfonate‐merocyanine (MEH) [85] . As it has been previously reported, [66] MEH can be irradiated by 420 nm light and transforms to transient anionic SP.…”
Section: Applications Of Dissipative Self‐assemblymentioning
confidence: 92%
“…Developing advanced stimulus-responsive materials is a crucial strategy to combat these challenges. 1 To date, numerous intelligent materials for information protection and anti-counterfeiting have been developed, 2 with fluorescence systems responsive to external stimuli such as temperature, 3 light, 4 pH, 5 and solvent 6 garnering substantial research interest.…”
Section: Introductionmentioning
confidence: 99%